Estudio de Vidrio Reciclado como componente para la Elaboración de Cementos Terciarios - Espinoza-Rivero, Edwin A. (Instituto Tecnológico de Costa Rica, 2017)
With cement production accounting for approximately 9% of the industrial production of greenhouse gases, and in order to generate alternative cementitious materials, this project presents the results of research aimed at developing cementants that potentially represent an environmentally sustainable alternative in civil construction. Combinations of different dosages of Glass Powder (GP, terminology taked from the publication “Performance of Glass-Powder concrete in Field Sites” from the 13° conference of ACI) were used to evaluate and study the compressive and tensile strength, as well as time of setting and normal consistency in mortars. The results obtained show that the strengths of the mixtures of cement and GP are suitable for a large number of applications in civil construction, and although in several cases the samples with GP do not have the same mechanical properties as their homologues (the results of some specimens are below their control without GP), the results obtained showed great potential for certain industrial applications. In addition to the compressive and tensile strength, these mixtures were determined their rheological properties defining their characteristics of flow and workability.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2017.
Keywords: Cemento; Vidrio en polvo; Resistencia; Flujo